Penerapan Media Flashcard Dalam Pembelajaran Membaca Siswa Kelas Dua - Riesta Monic Valentina; Sukartono (Program Studi Manajemen Pendidikan, 2023)
This research focuses on the application of flashcard media in the beginning reading learning of grade 2 students at SDN 02 Brujul. The study uses interviews, observation, and documentation to gather data from five grade 2 teachers and students. The research identifies learning planning activities such as selecting learning methods, preparing media, and teaching materials. The application of flashcard media involves learning letters in series I, II, and III. Factors inhibiting the application of flashcard media include family factors, while supporting factors include teacher, student, and infrastructure factors. To address these factors, diligent practice at home and coordination with parents regarding child development can be implemented. The study highlights the importance of considering both supporting and inhibiting factors in the application of flashcard media in early reading learning.